The Price Bundling of Services: A Normative Framework - Guiltinan, Joseph P. (Journal of Marketing, 1987)
As product lines have broadened in many industries (particularly service industries), the use of mixed price bundling has increased. In mixed price bundling, a firm offers its customers the choice of buying one or more products/services individually or of buying a “bundle” of two or more products or services at a special discount. The author presents a normative framework for selecting appropriate types of services for different mixed-bundling discount forms. The framework extends the economic theory of bundling (which historically has been applied to tie-in sales) to permit explicit consideration of different types of complementarity relationships and strategic marketing objectives.